New Light on the Mouton-Natoire Case (1768): Freedom of Conscience and the Role of the Jansenists - O'brien, Charles H. (A journal of church and state, 1985)
Charles H. O'brien; New Light on the Mouton-Natoire Case (1768): Freedom of Conscience and the Role of the Jansenists, Journal of Church and State, Volume 27, I